(untitled) (Indo-MathEdu Intellectuals Journal, 2023)
The purpose of this study is to develop digital comic media based on the Canva application, in terms of the feasibility and benefits of learning media in the research learning process used in this study is a type of research and development or Research and Development (R&D). The development of this media used procedures from ADDIE (Analysis, Design, Development, Implementation and Evaluation). The subjects in this study were 1 class teacher and 15 students who were directly involved in the teaching and learning process every day. As well as 1 material expert and 1 media expert. Data collection was carried out by means of: observation, questionnaires, interviews, and tests. The results showed that the Canva Application-Based Digital Comics media was "Very Eligible" with details of the eligibility percentage obtained from media experts of 88% with the criteria of "Very Eligible", material experts of 84% with the criteria of "Very Eligible", Education practitioners (teachers) by 94% with the criteria of "Very Practical", education practitioners (students) by 92% with the criteria of "Very Practitioner", and student learning outcomes after using digital comic media based on the Canva application have increased with the acquisition of a post-test score of 87.5% with the criteria of "Effective". Therefore, it can be concluded that digital comic media based on the Canva application on theme 6 sub-theme 2 learning 2 on PPKn class III content at SDN 064017 Medan Perjuangan District is feasible to use in the process of teaching and learning activities